An Analysis of Interference from Javanese in the Pronunciation of ï›ï”ï, ï›ï„ï and ï›ï‚£ï in English by the Students of Faculty of Letters in Gajayana University. - Pradnya Pramita Dewi (Journal of English Language Teaching and English Linguistics, 2014)
English as one of the international languages has been learned by the students of Faculty of Letters in Gajayana University. In learning English as foreign language, most learners have problem in pronunciation, especially in the way they pronounce the sound of the target language. Mispronunciations which are produce by the learners is caused by the interference of the source language or first language. The object of this research is the students of Faculty of Letters in Gajayana University 2005/2006 intake who are native speakers of Javanese and have been done phonology class. Some specific sounds are discussed in these research namely English sounds of inter-dental fricativeï›ï”ï, ï›ï„ï and alveolar approximantï›ï‚£ï. The finding of the research are some interferences occur in pronouncing those sounds, they are 1) voiceless inter-dental fricative ï›ï”ï is pronounced using voiceless dental stop ï›ï´ïƒï, aspirated voiceless dental stop ï›ï´ïƒï‚Žï, voiced dental stop ï›ï¤ïƒï, and voiceless palato-alveolar affricate ï›ï‚µï“ï. 2).Voiced inter-dental fricative is pronounce using voiceless dental stop ï›ï´ïƒï, aspirated voiceless dental stop ï›ï´ïƒï‚Žï, voiced dental stop ï›ï¤ïƒï, and voiceless palato-alveolar affricate ï›ï‚µï“ï. 3).Voiced alveolar approximant ï›ï‚£ï is pronounced using voiced alveolar trillï›ï²ï. 4). the possible reasons for the interferences made are based on the similarity of characteristics in the state of vocal cords, place of articulation, and manner of articulations.